1988
DOI: 10.1099/00207713-38-1-74
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma anseris sp. nov. Found in Geese

Abstract: A mycoplasma designated strain 1219T (T, type strain) was isolated from the phallus of a gander in Hungary. It was assigned to the class Mollicutes, order Mycoplasmatales, on the basis of morphological, cultural, and physical studies. The base composition of its deoxyribonucleic acid was 25 mol% guanine plus cytosine. It was dependent on sterol for growth, and its growth was inhibited by digitonin. The organism was assigned to the genus Mycoplasma since it did not hydrolyze urea and there was no evidence of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Several species of Mollicutes have been detected in geese: M. anatis (Gaillard-Perrin et al, 1983), M. anseris (Bradbury et al, 1988), M. cloacale (Stipkovits et al, 1984b), Mycoplasma gallinarum (Stipkovits et al, 1975), M. gallisepticum (Buntz et al, 1986;Benčina et al, 1987;Levisohn & Kleven, 2000), M. synoviae (Benčina et al, 1987), Mycoplasma imitans (Bradbury et al, 1993) and A. laidlawii and Acholeplasma axanthum (Stipkovits et al, 1975). However, on the basis of serological and biochemical studies, most of our isolates were identified as Mycoplasma sp.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several species of Mollicutes have been detected in geese: M. anatis (Gaillard-Perrin et al, 1983), M. anseris (Bradbury et al, 1988), M. cloacale (Stipkovits et al, 1984b), Mycoplasma gallinarum (Stipkovits et al, 1975), M. gallisepticum (Buntz et al, 1986;Benčina et al, 1987;Levisohn & Kleven, 2000), M. synoviae (Benčina et al, 1987), Mycoplasma imitans (Bradbury et al, 1993) and A. laidlawii and Acholeplasma axanthum (Stipkovits et al, 1975). However, on the basis of serological and biochemical studies, most of our isolates were identified as Mycoplasma sp.…”
Section: Discussionmentioning
confidence: 97%
“…Agar plates were incubated at 378C for 14 days and examined every 2 days for the appearance of mycoplasma colonies. Mycoplasma isolates were identified by indirect immunofluorescence (Bradbury, 1998) using rabbit antisera against M. anseris (Bradbury et al, 1988), M. cloacale (Bradbury & Forrest, 1984) and Mycoplasma sp. strain 1220 (Stipkovits et al, 1984b).…”
Section: Methodsmentioning
confidence: 99%
“… M. anseris causes airsacculitis, peritonitis, and embryo lethality ( 4 ) and probably has a role in cloaca and phallus inflammation of ganders ( 5 ). The type strain was isolated from a flock with a history of phallus inflammation ( 6 ). The M. cloacale type strain was isolated from a turkey ( 7 ), but this species could be isolated from ducks and geese as well ( 8 , 9 ).…”
Section: Announcementmentioning
confidence: 99%
“…species have been culturally isolated from geese over the past 18 years, including M. anatis (GAILLARD-PERRIN et al, 1983), M. cloacale (BRADBURY et a]., 1987), M . gallinarum (STIPKOVITS et al, 1975), M. anseris (BRADBURY et al, 1988), M . gallisepticum (BUNTZ et al, 1986), M .…”
Section: Introductionmentioning
confidence: 99%